Dielectric barrier discharge plasma treatment affects stability, metal ion coordination, and enzyme activity of bacterial superoxide dismutases. Issue 10 (27th May 2020) - Krewing, Marco; Jung, Christoph K.; Dobbelstein, Elena; Schubert, Britta; Jacob, Timo; Bandow, Julia E.
Abstract: A molecular‐level understanding of the effects of atmospheric‐pressure plasma on biological samples requires knowledge of the effects on proteins. Superoxide dismutases, which detoxify superoxide under oxidative stress conditions, play a key role in bacterial plasma resistance. Investigation of the impact of dielectric barrier discharge (DBD) treatment on purified superoxide dismutases SodA and SodB of Escherichia coli showed that DBD treatment caused a rapid protein degradation, with only 8% of protein remaining after 10 min. The affinity of SodA for the metal cofactor Mn 2+ was reduced. Mass spectrometry, in conjunction with coupled‐cluster calculations, revealed that modifications of amino acid residues in the active site can explain the decreased metal affinity and a distortion of the coordination geometry responsible for the activity loss. Abstract : All three superoxide dismutases (SODs) of Escherichia coli contribute to basal dielectric barrier discharge (DBD) plasma resistance. Purified SODs retain 50% activity after 1‐min DBD treatment. Histidine modifications in the active center affect metal cofactor coordination. The use of SODs as superoxide scavengers in plasma experiments is limited by protein stability and increasingly unspecific scavenging, as SODs are being modified by plasma.